Genetic Parameter Estimation for Breeding Soundness Examination Traits in Angus Bulls - Danielle M. Ellinghuysen (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objectives of this study were to estimate heritabilities, repeatabilities, and genetic relationships between scrotal circumference and semen quality traits to better understand their potential application in bull fertility genetic evaluation. Study Description: Eleven purebred Angus breeders provided 5,877 breeding soundness examination records on 4,996 bulls. The data included measurements of scrotal circumference, percentage of motility, gross motility score, percentage of primary abnormalities, percentage of secondary abnormalities, percentage of normal spermatozoa, and percentage of abnormal spermatozoa. Genetic parameters were estimated with statistical software also used by the American Angus Association for genetic evaluations. The Bottom Line: These results indicate that it is feasible to improve bull fertility with genetic selection, but further research is needed to determine the best methods for developing a commercially available genetic evaluation for bull reproduction.
Keywords: bull; fertility; genetics